Identifying and addressing uncertainties regarding the tapering of psychiatric medications - Boland, Miriam (Trinity College Dublin. School of Pharmacy & Pharma. Sciences. Discipline of Pharmacy, 2025)
Background: There is a cohort of individuals looking to discontinue use of psychiatric medication. Tapering is the recommended approach for reducing and/or stopping the use of psychiatric medication. This involves gradually reducing the dose of the medication over time to minimise the potential for withdrawal symptoms. However, many uncertainties exist regarding the process of reducing and stopping psychiatric medication. The main aim of this thesis was to develop a body of knowledge that would advance the evidence-base relating to the appropriate tapering of psychiatric medication. Methods: This thesis comprises four key studies comprising: a Priority Setting Partnership (PSP) Study to identify the Top 10 priorities for future research on reducing and stopping psychiatric medication in collaboration with three key stakeholder groups (i.e., people with lived experience of taking and/or stopping psychiatric medication, family members/friends/carers/supporters, and healthcare professionals) (Study 1); a qualitative descriptive analysis of free-text responses submitted to one of the PSP surveys to explore stakeholders' views and experiences of reducing and stopping psychiatric medication (Study 2); a qualitative descriptive study involving interviews with stakeholders who had participated in Study 1 to explore their views on the PSP methodology as a priority setting exercise (Study 3); and a scoping review to examine the content, underpinning evidence base, and impact of mobile phone apps and app-based interventions that supported the tapering of psychiatric medication (Study 4). Results: Study 1 co-produced the Top 10 list of research priorities on reducing and stopping psychiatric medication. The most highly ranked questions focused on the optimal tapering methods and supports and educating healthcare professionals about reducing/stopping psychiatric medication. Study 2 reported on stakeholders' views and experiences of various points of the withdrawal process, including their motivations for wanting to reduce/stop psychiatric medication, the challenges, and adverse effects they faced upon and after stopping the medication. Data were grouped into eight major themes. Study 3 captured stakeholders' thoughts on multi-stakeholder involvement, and how the PSP study achieved authentic collaboration between the three stakeholder groups. Four major themes were identified across the interview data. Study 4 identified a limited number of commercially available apps targeting individuals looking to taper psychiatric medication, as well as a deficit of studies evaluating any such apps in the literature. Conclusion: The main contribution of this thesis to the existing literature was through the development of a list of research questions and uncertainties about reducing and stopping psychiatric medication that will help guide future research and deliver responsive and strategic allocation of research resources. Other contributions include the insights into stakeholders' experience of stopping psychiatric medication captured by Study 2 which will encourage reflection on the role of these medications in mental illness, and the findings from the qualitative interviews with key stakeholders in Study 3 which will inform the methodology of future PSP studies. Finally, the findings from the scoping review in Study 4 which will guide the development of apps to support the tapering of psychiatric medication.
APPROVED
Keywords: antipsychotics; benzodiazepines; discontinuation; mental disorders; tapering; withdrawal; psychiatric medication; antidepressants